Toll-like receptor triggering augments activation of human mast cells by anti-citrullinated protein antibodies. Issue 10 (12th May 2014) - Suurmond, J; Rivellese, F; Dorjée, A L; Bakker, A M; Rombouts, Y J P C; Rispens, T; Wolbink, G; Zaldumbide, A; Hoeben, R C; Huizinga, T W J; Toes, R E M
Abstract : Objective: Mast cells may play a role in rheumatoid arthritis (RA), but activation of human mast cells in autoimmune settings has been little studied. Toll-like receptors (TLR) and Fcγ receptors (FcγR) are important receptors for cellular activation in the joint, but expression and stimulation of these receptors in human mast cells or the functional interplay between these pathways is poorly understood. Here, we analysed triggering of human mast cells via these receptors in the context of anti-citrullinated protein antibody-positive (ACPA+) RA. Methods: RNA and protein expression of TLRs and FcγR was quantified using PCR and flow cytometry, respectively. Mast cells were stimulated with TLR ligands (including HSP70) combined with IgG immune complexes and IgG-ACPA. Results: Human mast cells expressed TLRs and produced cytokines in response to TLR ligands. Both cultured and synovial mast cells expressed FcγRIIA, and triggering of this receptor by IgG immune complexes synergised with activation by TLR ligands, leading to two- to fivefold increased cytokine levels. Mast cells produced cytokines in response to ACPA immune complexes in a citrulline-specific manner, which synergised in the presence of HSP70. Conclusions: Our data show that synovial mast cells express FcγRIIA and that mast cells can be activated by IgG-ACPA and TLR ligands. Importantly, combined stimulation via TLRs and immune complexes leads to synergy in cytokine production. These findings suggest mast cells are important targets for TLR ligands and immune complexes, and that combined activation of mast cells via these pathways greatly enhances inflammation in synovial tissue of RA patients.